First-Principles Study of Pressure-Induced Phase Transitions and Electronic Properties of Ag2MoO4 - Beltran, Armando; Gracia, Lourdes [UNESP]; Longo, Elson [UNESP]; Andres, Juan (Amer Chemical Soc, 2014)
We have performed a systematic first-principles investigation by using the density functional formalism with the nonlocal B3LYP approximation to calculate structural and electronic properties as well as phase transitions under pressure of silver molybdate, Ag2MoO4. Five phases have been considered: tetragonal Ag2MoO4 (with normal and inverse P4(1)22 structures), beta-Ag2MoO4 (cubic spinel structure), olivine-type (orthorhombic structure), and alpha-Ag2MoO4 (tetragonal K2NiF4-type structure). Numerical and analytical fittings have been conducted to determine the equilibrium unit cell geometry and equation-of-state parameters for all structures and compounds involved in the phase diagram. Pressure dependencies of band structures, energy gaps, density-of-states (DOS), and vibrational frequencies were investigated. Theoretical results show that the inverse Ag2MoO4 with P4(1)22 symmetry is more stable above 15 GPa than the normal spinel structure, while the tetragonal structure is slightly more stable than the cubic representation above 6 GPa due to a tetragonal distortion. We determined the stability against decomposition of Ag2MoO4 toward binary oxides (MoO2, MoO3, Ag2O, AgO, and Ag2O3), metal (Ag and Mo), oxygen, and Ag2Mo2O7. Theoretical results point out that beta-Ag2MoO4 can decompose into Ag2Mo2O7 and Ag2O at 12 GPa.